Donor Site Morbidity after Anterior Iliac Bone Graft Harvesting - Rahadyan Magetsari (Journal of Global Pharma Technology, 2020)
Bone substitutes are being increasingly used especially in oncologic surgery, traumatology, revision prosthetic surgery and spine surgery. Bone substitute can be defined as a synthetic, inorganic or biologically organic combination which can be inserted for the treatment of a bone defect instead of autogenous or allogenous bone. Despite the improvement of research, human bone grafts persist to be the most effective bone substitutes to replace bone loss. This research was retrospective study conducted in consecutive sampling in Sardjito General Hospital Yogyakarta from January 2014 to Desember 2018. Patients underwent anterior iliac crest bone graft harvesting was included. 4 months after the procedure, the donor site morbidity was identified. The parameters used in this study are pain score using visual analog scale, paresthesia, problem in walking, wound infection, scar satisfaction and major morbidity. Anterior iliac bone graft harvesting resulted in minimal morbidity and neither pain or functional limitations. It also provides the optimal bone graft material, yields minimal morbidity, and is an acceptable choice in autologous bone graft harvesting.